A Family Affected by a Life-Threatening Erythrocyte Defect Caused by Pyruvate Kinase Deficiency With Normal Iron Status: A Case Report - Maciak, Karolina; Adamowicz-Salach, Anna; Poznanski, Jaroslaw; Gora, Monika; Fronk, Jan; Burzynska, Beata (Frontiers in Genetics, 2020)
Background: Red cell pyruvate kinase deficiency (PKD) is a defect of glycolysis causing congenital non-spherocytic hemolytic anemia. PKD is transmitted as an autosomal recessive trait. The clinical features of PKD are highly variable, from mild to life-threatening anemia which can lead to death in the neonatal period. Most patients with PKD must receive regular transfusions in early childhood and as a consequence suffer from iron overloading. Patient: Here, we report a Polish family with life-threatening hemolytic anemia of unknown etiology. Whole exome sequencing identified two heterozygous mutations, c.1529 G>A (p.R510Q) and c.1495 T>C (p.S499P) in the PKLR gene. Molecular modelling showed that the both PKLR mutations are responsible for major disturbance of the protein structure and functioning. Despite frequent transfusions the patients do not show any signs of iron overload and hepcidin, a major regulator of iron uptake, is undetectable in their serum. The patients were homozygous for the rs855791 variant of the TMPRSS6 gene which has earlier been shown to down-regulate iron absorption and accumulation. Conclusion: The lack of iron overload despite a reduced level of hepcidin in two transfusion-dependent PKD patients suggests the existence of a hepcidin-independent mechanism of iron regulation preventing iron overloading.